Myocarditis Screening Methods in Athletes After SARS-CoV-2 Infection – a Systematic Review - Hofbauer, Theresa; Humann, Kathrin; Neidenbach, Rhoia Clara; Scharhag, Jürgen (International Journal of Sports Medicine, 2023)
This review aims to elucidate the myocarditis incidence in SARS-CoV-2-positive athletes and to evaluate different screening approaches to derive sports cardiological recommendations after SARS-CoV-2 infection. The overall incidence of athletes (age span 17–35 years, 70% male) with myocarditis after SARS-CoV-2 infection was 1.2%, with a high variation between studies (which contrasts an incidence of 4.2% in 40 studies within the general population). Studies that used conventional screening based on symptoms, electrocardiogram, echocardiography, and cardiac troponin – only followed by cardiac magnetic resonance imaging in case of abnormal findings – reported lower myocarditis incidences (0.5%, 20/3978). On the other hand, advanced screening that included cardiac magnetic resonance imaging within the primary screening reported higher incidences (2.4%, 52/2160). The sensitivity of advanced screening seems to be 4.8 times higher in comparison to conventional screening. However, we recommend prioritization of conventional screening, as the economical load of advanced screening for all athletes is high and the incidence of myocarditis in SARS-CoV-2-positive athletes and the risk of adverse outcomes seems low. Future research will be important to analyze the long-term effects of myocarditis after infection with SARS-CoV-2 in athletes for risk stratification to optimally guide a safe return to sport.
Keywords: return to sport; COVID-19; CMR; review